(3GdJNWjW GdGSJQGJjLj ddehGQO GdHTQjI aj GdbWGY GdYGe (B:s (3GdCQOf CfehPLG (B/s - (3GdVehQ, ehab eMeOs ((3GdCQOf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2011)
(3jVe GdJNWjW GdGSJQGJjLj aj GdbWGY GdYGe,eaghe GdJNWjW GdGSJQGJjLj, GdJNWjW GdGSJQGJjLj aj GdbWGY GdYGe, EOGQI GdehGQO GdHTQjI aj GdbWGY GdYGe, hGdJNWjW GdGSJQGJjLj ddehGQO GdHTQjI aj GdbWGY GdYGe aj GdCQOf, hGbY GdJNWjW GdGSJQGJjLj ddehGQO GdHTQjI aj GdbWGY GdYGe aj GdCQOf HeG ajgG efgLjI GdOQGSI hGdOQGSGJ GdSGHbI hGdOQGSI GdejOGfjI hehbYgG Hjf GdOQGSGJ, fJGFL JMdjd HjGfGJ GdOQGSI, GdfJGFL hGdJhUjGJ(B.s
(3HjHdjhZQGajG(B: (3U U(B.195-201s
Keywords: (3GdJNWjWs; (3GdbWGY GdYGes; (3Gdbhi GdYGedIs